Substituent Pattern Effects on the Redox Potentials of Quinone‐Based Active Materials for Aqueous Redox Flow Batteries. Issue 20 (23rd September 2020) - Schwan, S.; Schröder, D.; Wegner, H. A.; Janek, J.; Mollenhauer, D.
Abstract: Quinone‐based, aqueous redox flow batteries are a promising technology for large‐scale, low‐cost energy storage. To understand the influence of substituent and substituent pattern effects of quinone‐based derivatives on the redox potential, a screening study was performed that included benzoquinone, naphtaquinone, and anthraquinone derivatives. The order of substituent influence is −OH>−Me/−OMe for decreasing the redox potential and −F<−SO3 − <−CN, −NO2 for increasing the redox potential, which is in agreement with general expectations. We found that the consideration of resonance and inductive effects design strategies of redox‐active materials can be extended by the ability of intramolecular hydrogen bond formation, steric hindrance, and energetic differences of conformers for oxidized and reduced species. Due to the complexity and overlap of these effects, theoretical screening studies can provide guidance for the design of new molecular materials. In addition to the redox potential, other parameters such as stability, solubility, and kinetic rate constant or synthetic accessibility are crucial to consider. Abstract : A computational screening study has been performed in order to understand and optimize substituent pattern effects of quinone‐based redox‐flow systems. Therefore, the type, number, and position of substituents at benzo‐, naphto‐ and anthraquinione derivatives has been investigated.